Effectiveness of a modified version of the applied relaxation technique in treatment of perimenopausal and postmenopausal symptoms - Saensak S; Vutyavanich T; Somboonporn W; Srisurapanont M (International Journal of Women's Health, 2013)
Suprawita Saensak,1,2 Teraporn Vutyavanich,3 Woraluk Somboonporn,4 Manit Srisurapanont5 1Academic Department, Faculty of Medicine, Mahasarakham University, Maha Sarakham, 2Department of Community Medicine, Faculty of Medicine, Chiang Mai University, Chiang Mai, 3Department of Obstetrics and Gynecology, Chiang Mai University, Chiang Mai, 4Department of Obstetrics and Gynecology, KhonKaen University, KhonKaen, 5Department of Psychiatry, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand Background: Awareness of the risks associated with hormone therapy for menopausal symptoms has sparked a global decline in this treatment. Alternative treatments to relieve menopausal symptoms are therefore required. The applied relaxation (AR) technique has proven to be successful for symptom amelioration, but requires participation in 12 weekly classes. The purpose of this study was to determine the effectiveness of a modified relaxation version (MR) of AR for treatment of hot flashes, night sweats, and sleep disturbances. Methods: We conducted a12-week, randomized, parallel, open-label, controlled trial in perimenopausal and postmenopausal women visiting the menopausal clinic. Participants were randomly assigned to an MR or AR group. The MR group (n=36) received a single session of (MR) training and the AR group (n=35) received conventional 12-week training. Participants were instructed to practice the techniques daily at home for 12 weeks. The main outcome was the measure on the severity scale and frequency of hot flashes, night sweats, and sleep disturbances. Results: All participants completed the study. Total severity scores in both groups decreased after 12 weeks, but there was no difference between the groups (P=0.93). The severity score for hot flashes in the MR group decreased more than in the AR group (P=0.02). The severity scores for night sweats and sleep disturbances decreased in both groups. The frequency of hot flashes, night sweats, and sleep disturbances were also decreased in both groups. Conclusion: A shorter, modified version of the AR was equally effective or slightly better than the conventional AR for the relief of hot flashes, night sweats, and sleep disturbances in perimenopausal and postmenopausal women. Recommendations for future research include confirmatory studies and trials with larger samples. Keywords: alternative treatments, applied relaxation, menopausal symptoms, hot flashes